The Leadership Behavior of Madrasah Principals in Improving the Quality of Education in MAN 3 Medan - Muhammad Fuad Zaini; Syafaruddin Syafaruddin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article aimed to determine the existing leadership behavior in the school as an effort to improve the quality of education by implementing programs, communication, and motivation. This research used qualitative methods in case study. The researchers used triangulation, observation, interviews, and documentation in data collecting methods. The results showed that the implementation of activity programs such as training can improve the quality and professionalism of teachers. Coaching extracurricular activities can add insight and soft skills to students. The implementation of the Adiwiyata Dimadrasah program aimed at creating awareness of loving the environment and as a place for learning. The communication applied by the principal was interpersonal communication, two-way, and feedback. The form of motivation towards madrasah citizens was exemplified by performance, professional, procedural and agents of change. Keywords: Leadership, Quality of Education, Teacher Professionalism